Epidemiology and Antibiogram Profiles of Respiratory Tract Infections in Goats - Bhoya, Shruti D; Mehta, Sudhir A; Makwana, Pushpa; Patel, Manish D; Vala, Jignesh B; Patel, Mayank A (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Respiratory tract infections (RTIs) are the most common disease manifestations among goat population. In present study, the overall incidence of RTIs in goats of south Gujarat recorded was 27.75 % (126/454). The highest incidence of RTIs was recorded in goats aged below 6 months and in male goats. Non-descript and Surti breed of goats were clinically more susceptible to disease than other breeds. Seasonal peaks were observed in February and June. Clinically, infected goats exhibited elevated rectal temperature, heart rate, pulse rate, respiratory rate and capillary refill time, along with significant low saturation of peripheral oxygen (SpO2). Bacteriological analysis identified Staphylococcus spp. as the most common pathogen, followed by Streptococcus spp., mixed infections (Staphylococcus Streptococcus spp.), Pseudomonas spp., Escherichia coli and Micrococcus spp. Antibiotic sensitivity testing revealed that Staphylococcus spp. was highly sensitive to amikacin, streptomycin and penicillin. Streptococcus spp. responded well to streptomycin, ceftriaxone tazobactam and penicillin, while mixed infections were sensitive to amoxiclav, moxifloxacin and ceftriaxone-tazobactam. Pseudomonas spp. was sensitive to amikacin and ceftriaxone-tazobactam, Escherichia coli to enrofloxacin, penicillin and moxifloxacin and Micrococcus spp. to oxytetracycline, enrofloxacin and ceftriaxone-tazobactam. These findings provide essential insights for effective diagnosis and targeted treatment of RTIs in goats.